The Scale and Extent of Political Economies of the Middle Bronze Age Jazīrah and the Bilād al-Šām (c. 1800-1600 BCE) - Rattenborg, Rune ; 0000-0002-1422-9645 (2016)
The present thesis investigates the material scale of six political economies distributed across the dry-farming plains and piedmonts of the Middle Bronze Age Jazīrah and the Bilād al-Šām. This is done using a comparative and interdisciplinary approach combining the large-scale analysis of administrative cuneiform texts with the compilation of relevant archaeological survey datasets. Drawing on theories and methods developed in landscape archaeology and historical sociology, the thesis builds a regional analysis of economic scale through a focus on three analytical units; the institutional household, the parent site, and the associated micro-region. Based on a dataset extracted from c. 1500 administrative cuneiform texts from the six study sites, the analytical chapters present a comprehensive discussion of the socio-economic and technological context of chief agricultural and animal resources and the material scale of their production, manipulation, circulation, and consumption. These investigations are undertaken focusing on three spheres of social action, namely the urban neighbourhood, agricultural regimes, and livestock management. The analysis concludes by drawing together quantitative data on various aspects of the institutional household economy to assess its material scale relative to the subsistence needs of its parent site and associated micro-region. The thesis demonstrates the limited material capabilities of a group of early political organisations relative to their social setting, both at the level of the parent settlement and, more forcefully, at the surrounding hinterland. It underscores the role of nascent political organisations as local and very resilient economic infrastructures across a politically volatile period of Bronze Age history. In line with recent and comparable investigations on Bronze Age economies, these findings offer critical revisions of traditional notions of the power of the early state. In methodological terms, the thesis formulates a novel means of combining large-scale analyses of text and material culture at a regional level, which can be applied in future studies.